Optimal duration of stretching exercise in patients with chronic myofascial pain syndrome: A randomized controlled trial - Sameeha S. Mansoori; Ibrahim M. Moustafa; Amal Ahbouch; Deed E. Harrison (Medical Journals Sweden, 2021)
Objective: To explore the effect of variable durations of stretching on neural function, pain, and algometric pressure in patients with chronic myofascial pain syndrome. Design: Randomized controlled trial. Patients: A total of 100 participants diagnosed with chronic myofascial pain syndrome were randomly assigned to a control group or 1 of 3 intervention groups. Methods: The 3 experimental groups received different durations of cervical spine stretching: 15, 30 or 60 s. The control group did not stretch. Primary outcome measures included peak-to-peak somatosensory-evoked potential for dermatomes C6, C7 and C8. Secondary outcome measures included central somatosensory conduction time (N13-N20), pain intensity, and pressure-pain threshold algometric measurements. All outcome measures were assessed immediately after and 2 h after the treatment session. Results: Post hoc analysis indicated that stretching for 60 s significantly decreased the dermatomal amplitude for C6, C7 and C8 (p < 0.001) and significantly increased the central conduction time, indicating negative effect (p < 0.001). Stretching for 30 and 60 s resulted in greater improvement in pain intensity and algometric pressure than stretching for 15 s or no stretch (control) p < 0.001. Conclusion: Stretching cervical muscles involved in chronic myofascial pain syndrome for 30 s was optimal in achieving stretching benefits and minimizing the negative effects on the neural function of the involved nerve roots and central nervous system.